The financing of small-scale enterprises in Uganda - Bosa, George R. (Nairobi : Published for the Makerere Institute of Social Research by Oxford University Press, 1969)
This study presents a comprehensive survey of the main sources of funds available to small enterprises in Uganda and the problems and difficulties encountered by the small firms.
Includes bibliographical references: p. [103]-105.
asm 24/01/2019
Loans
Keywords: Small businesses; Small business--Finance; Uganda